School absenteeism, academic performance, and self-esteem as proxy measures of oral health status: A cross-sectional study - Thiruvenkadam Gopalan; Sharath Asokan; J Baby John; P R Geetha Priya (Wolters Kluwer Medknow Publications, 2018)
Purpose: The purpose of the study was to assess the impact of school absenteeism, academic performances, and self-esteem of school-going children on their oral health status. Materials and Methods: The study sample included 2014 children aged 12-15 years from India. Rosenberg self-esteem scale was used to assess the self-esteem of the children. Data on school performance, homework completion, and absenteeism were obtained from the school authorities and parents. Clinical examination for each child was done to assess the Decayed, Missed, and Filled Teeth (DMFT) and Oral Hygiene Index-Simplified (OHI-S) scores. The data obtained were statistically analyzed using Pearson's Chi-square test, Mann-Whitney test, and Kruskal-Wallis test with the aid of SPSS software. Odds ratio was calculated with 95% confidence interval. P ≤0.05 was considered statistically significant. Results: Oral health had a significant association with school absenteeism and homework completion. School absenteeism was significantly associated with dental caries (P = 0.007) and poor oral hygiene (P = 0.001), whereas homework completion was significantly associated with dental caries alone (P = 0.002). There was no significant association between variables like self-esteem, first language, mathematics, and DMFT/OHI-S score. Conclusion: School records such as absenteeism data and homework completion can be used as proxy measures of the oral health status in children.